Kontribusi Kecerdasan Spiritual dan Dukungan Keluarga Terhadap Kepuasan Hidup Lansia Serta Implikasinya Dalam Pelayanan Bimbingan dan Konseling - Ramdani Ramdani; Daharnis Daharnis; Syahniar Syahniar (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2016)
Life satisfaction on the Elderly were influenced by various factors. This study aims to describe: 1).the level of life satisfaction, spiritual intelligence and Elderly family support, 2) the contribution of spiritual intelligence and family support either individually or jointly to the Elderly life satisfication. The research population were the elderly in the city of Padang, with samples are 60 people, by using non probability sampling techniques. The instruments used in the research is the Likert scale model. Reliability test results on spiritual intelligence was 0.844; while the family support and life satisfaction are each valued at 0.542 and 0,871. The results of the validity of the average instrument for spiritual intelligence 0,542, familie supports and life satisfaction are each valued at 0.510 and 0,492. The results of this study showed that spiritual intelligence, family support and life satisfaction were in high requirements for the Elderly life satisfaction and the spiritual intelligence and support families either singly or together were contributing to the Elderly life satisfaction.Keywords : Elderly, Spiritual Intelligence, Family Support, Life Satisfaction